A laboratory‐based evaluation of tube blocking and microbial risks associated with one blended enteral feed recipe. Issue 5 (3rd July 2019) - Madden, A. M.; Baines, S.; Bothwell, S.; Chen, E.; Goh, S.; Jerome, L.; Sommariva‐Nagle, C.; Szychta, M.
Abstract: Background: Concerns associated with blended enteral feeds include the risk of blocked tubes and microbial contamination, although the available evidence is limited. The present laboratory‐based investigation aimed to examine these risks in a blended feed providing a nutritionally adequate intake for a hypothetical patient. Methods: A one‐blended feed recipe was made using three different methods (professional, jug and stick blenders) and three storage procedures. Feed samples were syringed via 10‐, 12‐ and 14‐French (Fr) enteral feeding tubes and both blockages and the time taken were recorded. Feed samples were diluted, plated on agars, incubated and bacterial colony‐forming units (CFU) counted. After storage at −80 °C, identification was undertaken using 16S rRNA polymerase chain reaction sequencing. Results: Two blockages occurred during 27 administrations of feed made using a professional blender, although they were resolved with a water flush. No blockages occurred with the 14‐Fr tube and administration was quicker with wider tubes ( P  < 0.00001). There was no significant difference between the total bacterial CFU of feeds prepared using different methods ( P  = 0.771) or stored differently. The genus of bacteria identified included Enterococcus, Bacillus, lactose‐fermenting Enterobacteriaceae, Pseudomonas and Staphylococcus . Pathogens, such as Clostridium spp., Salmonella spp. and Vibrio spp., were not identified by phenotypic tests used. Sequencing identified Escherichia coli, Shigella spp., Streptococcus lutetiensis and Staphylococcus epidermidis . Conclusions: The present study found no risk of tube blockages when one blended feed recipe made using three methods was delivered via a 14‐Fr tube. There is concern about bacterial contamination, although this was not influenced by the methods of preparation or storage used in the present study.